Use of wild edible plants: A comparative analysis of seven plant species for potential food applications - Ehsan Ali; Muhammad Farooq Azhar (Food and Humanity, 2026)

Diosgenin-loaded niosomes ameliorate cadmium-induced neurotoxicity and endocrine disruption in female rats through modulation of oxidative stress, apoptosis, and inflammatory markers - Kanza Hashmi; Ammara Saleem; Shakila Sabir; Shahana Ehsan; Aisha Mobashar; Muhammad Imran khan; Shahnaz; Zulcaif Ahmad; Muhammad Furqan Akhtar; Musaab Dauelbait; Amir Bouallegue; Esmael M. Alyami; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Improving subseasonal Indian summer monsoon rainfall forecasts with U-Net calibration - Emile D. Esmaili; Andrew W. Robertson; Muhammad Azhar Ehsan; Bohar Singh; Aaron Kaplan; Avijit Dey; Susmitha Joseph (Climate Dynamics, 2026)

Mineralogical characterization and rock physics parameter estimation in sandstone reservoir: A template-based approach and cross-plots analysis - Muhsan Ehsan; Muhammad Nofal Munir; Rujun Chen; Muhammad Ali; Kamal Abdelrahman; Ali Y. Kahal (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

AACVD-derived Co-Ni alloys for the efficient electrooxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid - Muthumariappan Akilarasan; Muhammad Ali Ehsan; Mohsin Pasha; Maryum Ali; Muhammad Nawaz Tahir; Muhammad Bilal Khan Niazi; Wasif Farooq (Journal of Environmental Chemical Engineering, 2026)

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Fiber type-specific expression of LACTB leverages a function in oxidative metabolism - Kirsi-Marja Alanen; Rabah Soliymani; Jaakko Sarparanta; Satu Kuure; Kirsi Sainio; Zydrune Polianskyte; Muhammad Yasir Asghar; Ehsan Zangene; Annunziata Cascone; Maciej Lalowski; Peter Hackman; Johan Lundin; et al. (Histochemistry and Cell Biology, 2026)
Skeletal muscle is composed of type I and type II fibers, each characterized by specific metabolic machinery. LACTB is a conserved mitochondrial protein implicated in lipid utilization and tumorigenesis, but its precise function in the cellular metabolism remains unclear. To gain novel insight into the functional role of LACTB, we investigated skeletal muscle to determine whether LACTB is segregated by fiber type. The expression of LACTB was determined by immunohistochemistry (IHC) and immunoblotting in skeletal muscle from healthy human subjects and the laboratory rat. The specificity of the antibody was assessed using recombinant human LACTB protein and endogenous LACTB in isolated mitochondria. IHC results were validated in a cellular model of myoblast differentiation using the C2C12 and L6 cell lines. The results demonstrated that LACTB is highly enriched in adult type I muscle fibers. During development, LACTB expression commences in type I primary myotubes at the time of their formation around week 20 of gestational age. LACTB expression in myoblasts is low but increases rapidly upon the induction of myotube differentiation. We conclude that LACTB plays a distinct role in mitochondria of type I fibers, most likely acting in oxidative metabolism related to energy use from lipids. This defines LACTB as a mitochondrial marker for type I fibers.

Assessment of urban and peri-urban grazing practices from herders and local community perspective in the semiarid region of Pakistan - Muhammad Farooq Azhar; Ghulam Yasin; Asghar Ali; Abida Aziz; Ghulam Yasin; Daniyal Hussain; Ehsan Ali (Environmental Monitoring and Assessment, 2026)

Advancing seismic facies analysis and reservoir characterization: A synthetic data-augmented CNN and transfer learning workflow integrated with real seismic data - Muhammad Ali; Ning Wei; He Changxingyue; Keyao Lin; Wendong Wang; Muhsan Ehsan; Ren Jiang; Wakeel Hussain; Umar Ashraf (Gas Science and Engineering, 2026)

Simultaneous quantification of hydroxycinnamate derivatives and antioxidant activity of Ziziphus oxyphylla Edgew. leaf methanolic extract - Surriya Naheed; Muhammad Wajid; Afsheen Ehsan; Khalid Hussain; Gulzar Muhammad; Naureen Shehzadi; Muhammad Tanveer Khan; Imran Ahmad; Adnan Ashraf (Natural Product Research, 2026)

Hermetic storage reduces postharvest losses in challenging ambient environments - Ehsan Khalid; Irfan Afzal; Muhammad Amir Bakhtavar (Journal of Stored Products Research, 2026)

Genetic Innovations in Soybean: Key Genes Driving Salinity Tolerance - Muhammad Hafeez Ullah Khan; Jabar Zaman Khan Khattak; Ali Muhammad; Ehsan Ali; Sajjad Ali; Shah Fahad; Xianzhong Feng (Journal of Plant Growth Regulation, 2026)

Zataria multiflora extract enhances imatinib-induced cytotoxicity in chronic myeloid leukemia and multiple myeloma cells - Sahar Mostajeran; Mohsen Ehsan; Mahla Lashkari; Hajar Mardani Valandani; Ahmad Fatemi; Ali Bazi; Mahdieh Mirzaie; Muhammad Hossein Ashoub; Roohollah Mirzaee Khalilabadi (Molecular Biology Reports, 2025)

Evaluating performances of SVR, HBA–SVR, and COOT–SVR techniques: monthly evaporation modeling in Algeria - Mohammed Achite; Muhammad Jehanzaib; Nehal Elshaboury; Muhammad Umar Khan; Kusum Pandey; Ehsan Mirzania (Euro-Mediterranean Journal for Environmental Integration, 2025)

Corrigendum to ‘Metal ferrites-based nanocomposites and nanohybrids for photocatalytic water treatment and electrocatalytic water splitting’ [Chemosphere 310 (2023) 136835] - Ahmad Farhan; Javeria Arshad; Ehsan Ullah Rashid; Haroon Ahmad; Shahid Nawaz; Junaid Munawar; Jakub Zdarta; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2025)

Comparison of surface and subsurface limestone reservoir properties: key insights derived from the analysis of geological and geophysical datasets - Muhsan Ehsan; Gohar Hammayun Khan Raja; Afifa Tassaduq; Waqas Naseem; Muhammad Ali; Kamal Abdelrahman; Ali Y. Kahal (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Multicriteria evaluation of cropland suitability using multisource datasets of satellite remote sensing and ground observation - Danish Raza; Hong Shu; Sahar Mirza; Hasnat Aslam; Aqil Tariq; Rana Waqar Aslam; Hafsa Aeman; Muhsan Ehsan; Maryam Muhammad Ali (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Geothermal investigation of sandstone reservoirs using a probabilistic neural network with 2D seismic and borehole data: insights into structural and reservoir characteristics - Zohaib Naseer; Muhsan Ehsan; Muhammad Ali; Kamal Abdelrahman; Yasir Bashir (Geothermics, 2025)

Corrigendum to “Production of manganese telluride-based manganese oxide nano-composite works as a catalyst for effective oxygen evolution reaction” [363 (2024) 130919] - Zainab M. Almarhoon; Karam Jabbour; Sumaira Manzoor; Syed Imran Abbas Shah; Muhammad Faheem Ashiq; Muhammad Yousaf Ur Rehman; Muhammad Fahad Ehsan; Muhammad Najam-ul-Haq; Muhammad Naeem Ashiq (Fuel, 2025)

Flower-like nanoscale Ni(OH)2/MnCO3 electrocatalyst for efficient hydrogen evolution reaction in wide pH range - Zobia Siddique; Salman Noshear Arshad; Muhammad Ali Ehsan; Faryal Aftab; Akhtar Munir; Suryyia Manzoor; Sadia Fatima; Farah Sajjad; Javed Ahmad; Hatice Duran; Senem Çitoğlu (Fuel, 2025)

Electrochemical activation of alum sludge for the adsorption of lead (Pb(II)) and arsenic (As): Mechanistic insights and machine learning (ML) analysis - Hye-Bin Kim; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Jong-Gook Kim (Bioresource Technology, 2025)

Geo-spatial distribution of air pollutants in urban area and its potential health risk analysis solutions - Fajar Waheed; Nusrat Ehsan; Rabiya Nasir; Waqas Ahmed Khan; Muhammad Fahim Khokhar; Laila Shahzad; Aqil Tariq; Hira Afzal; Qamar uz Zaman (Urban Climate, 2025)

An integrated comprehensive approach describing structural features and comparative petrophysical analysis between conventional and machine learning tools to characterize carbonate reservoir: A case study from Upper Indus Basin, Pakistan - Zohaib Naseer; Urooj Shakir; Muyyassar Hussain; Qazi Adnan Ahmad; Kamal Abdelrahman; Muhammad Fahad Mahmood; Mohammed S. Fnais; Muhsan Ehsan (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Simultaneous removal of Cr(VI), As(III), and sulfanilamide via an e-barrier electrochemical system: A pilot study - Jong-Gook Kim; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Kitae Baek (Journal of Hazardous Materials, 2025)

Hydropriming and Nano-Priming with Zinc and Iron Oxide Nanoparticles Improved Growth and Physio‑Biochemical Attributes of Sugarcane (Saccharum officinarum L.) Propagated Through Bud Nodes - Rafi Qamar; Syed Nasir Abbas; Atique-ur-Rehman; Hafiz Muhammad Rashad Javeed; Muhammad Ather Nadeem; Muhammad Ehsan Safdar; Muhammad Yaseen; Arkadiusz Artyszak; Mona S. Alwahibi; Manal Abdulaziz Binobead (Journal of Soil Science and Plant Nutrition, 2025)

Evaluation of cotton (Gossypium hirsutum L.) seed longevity and deterioration: Physiological and biochemical aspects in relation to moisture contents during storage in different module systems - Faryal Fatima; Ehsan Khalid; Irfan Afzal; Muhammad Usman; Muhammad Ather Nadeem; Muhammad Kamran (Journal of Stored Products Research, 2025)

Diagenetic and mineralogical impacts on clastic reservoir; A case study from the lower Indus Basin, Pakistan - Muhammad Nofal Munir; Mohammad Zafar; Muhsan Ehsan; Rujun Chen; Kamal Abdelrahman; Jar Ullah; Tassawar Hayat; Hamad Ur Rahim (Journal of Asian Earth Sciences, 2025)

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

Corrigendum to “Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications” [Fuel 357(Part A) (2024) 129688] - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2025)

Geophysical characterization for dolerite dykes (dimension stone) reserves exploration using electrical resistivity tomography (ERT) in Shergarh Oghi, Mansehra, Pakistan - Irfan Raza; Hashmat Ullah; Perveiz Khalid; Muhammad Zeerak Iqbal; Sania Rasheed; Muhammad Irfan Ehsan (Acta Geodaetica et Geophysica, 2025)

Attributing rainfall and drought variability across climate vulnerable area of Pakistan: Perspective from different satellite and ground-based datasets - Mohammad Ilyas Abro; Ehsan Elahi; Murad Ali Khaskheli; Rashid Mustafa Korai; Mahdi Hassan; Asghar Ali Majidano; Bhai Khan Solangi; Faiz Muhammad Khokhar (Theoretical and Applied Climatology, 2025)

Combined effect of abamectin and imidacloprid against three insects of cotton - Anam Ejaz; Ahmad Nawaz; Nazia Ehsan; Muhammad Jalal Arif (Journal of Plant Diseases and Protection, 2025)

An integrated geophysical and geotechnical solutions for assessing slope instability challenges in open-pit mining: safeguarding mining operations - Irfan Raza; Hashmat Ullah; Muhammad Irfan Ehsan; Perveiz Khalid; Muhammad Zeerak Iqbal; Sania Rasheed (Bulletin of Engineering Geology and the Environment, 2025)

Systematic review on buparvaquone resistance associated with non-synonymous mutation in drug binding genes site of Theileria annulate - Muhammad Rashid; Muhammad Hassan Hayat; Naveed Zahra; Mian Sayed Khan; Suleman; Muhammad Nadeem; Tauseef ur Rehman; Muhammad Ehsan; Muhammad Irfan Malik; Muhammad Kashif Obaid; Amir Bakhsh; Mohamed Aziz Darghouth; et al. (Veterinary Parasitology, 2024)

Machine learning trained poly (3,4-ethylenedioxythiophene) functionalized carbon matrix suspended Cu nanoparticles for precise monitoring of nitrite from pickled vegetables - Waseem Abbas; Farhan Zafar; Manal F. Abou Taleb; Mavra Ameen; Abdul Sami; Muhammad Ehsan Mazhar; Naeem Akhtar; Muhammad Waseem Fazal; Mohamed M. Ibrahim; Zeinhom M. El-Bahy (Food Chemistry, 2024)

Assessment of Machine Learning Algorithms for Land Cover Classification in a Complex Mountainous Landscape - Gomal Amin; Iqra Imtiaz; Ehsan Haroon; Najum us Saqib; Muhammad Imran Shahzad; Majid Nazeer (Journal of Geovisualization and Spatial Analysis, 2024)
Mapping land cover (LC) in mountainous regions, such as the Gilgit-Baltistan (GB) area of Pakistan, presents significant challenges due to complex terrain, limited data availability, and accessibility constraints. This study addresses these challenges by developing a robust, data-driven approach to classify LC using high-resolution Sentinel-2 (S-2) satellite imagery from 2019 within Google Earth Engine (GEE). The research evaluated the performance of various machine learning (ML) algorithms, including classification and regression tree (CART), maximum entropy (gmoMaxEnt), minimum distance (minDistance), support vector machine (SVM), and random forest (RF), without extensive hyperparameter tuning. Additionally, ten different scenarios based on various band combinations of S-2 data were used as input for running the ML models. The LC classification was performed using 2759 sample points, with 70% for training and 30% for validation. The results indicate that the RF algorithm outperformed all other classifiers under scenario S1 (using 10 bands), achieving an overall accuracy (OA) of 0.79 and a kappa coefficient of 0.76. The final RF-based LC mapping shows the following percentage distribution: barren land (46.7%), snow cover (22.9%), glacier (7.9%), grasses (7.2%), water (4.7%), wetland (2.9%), built-up (2.7%), agriculture (1.9%), and forest (1.2%). It is suggested that the best identified RF classifier within the GEE environment should be used for advanced multi-source data image classification with hyperparameter tuning to increase OA. Additionally, it is suggested to build the capacity of various stakeholders in GB for better monitoring of LC changes and resource management using geospatial big data.

Synergistic electro-thermal enhancement of nitrogen removal in an iron-based Anammox system at low temperatures - Fei Xie; Xiaogang Li; Philip Antwi; Li Ji; Muhammad Ehsan Danish; Bowei Zhao (Journal of Water Process Engineering, 2024)

Detection of Mobile and Immobile Solute Transport and Their Residence Time in Saturated Low and High Permeability Soil Layers - Muhammad Zaheer; Ehsan Ul Haq; Ning Huang; Ahmed Amara Konaté; Ghulam Mujtaba Shah; Raja Umer Sajjad; Saad Ahmed Mashwani (Water, Air, & Soil Pollution, 2024)

Analyzing policy implications by considering adoption barriers on consumer adoption intention for electric vehicles: a comprehensive overview - Farheen Ehsan; Salman Habib; Muhammad Majid Gulzar; Junhua Guo (Environment, Development and Sustainability, 2024)

Assessing the electrode configuration in a sandbox system for the removal of sulfanilamide: A pilot study - Jong-Gook Kim; Hye-Bin Kim; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Kitae Baek (Chemosphere, 2024)

Integrated study for assessing groundwater dynamics of the Dehdan village, Haripur Basin, Pakistan - Umair Bin Nisar; Siddique Akhtar Ehsan; Muhammad Imran Rafiq; Muhammad Rizwan Mughal (Journal of Applied Geophysics, 2024)

The Acute Impact of Propofol on Blood–Brain Barrier Integrity in Mice - Ehsan Nozohouri; Yeseul Ahn; Sumaih Zoubi; Dhavalkumar Patel; Sabrina Rahman Archie; Khondker Ayesha Akter; Muhammad Bilal Siddique; Juyang Huang; Thomas J. Abbruscato; Ulrich Bickel (Pharmaceutical Research, 2024)

In-situ groundwater remediation of contaminant mixture of As(III), Cr(VI), and sulfanilamide via electrochemical degradation/transformation using pyrite - Jong-Gook Kim; Stephanie Sarrouf; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Kitae Baek (Journal of Hazardous Materials, 2024)

Classification of aerosol types in mega-city of Lahore (Pakistan) using ground-based remote sensing - Muhammad Nabeel Khan; Salman Tariq; Nimra Ehsan; Tunjeena Haseeb (Air Quality, Atmosphere & Health, 2024)

Evaluation of drought hazards and coping strategies adopted by pastoral communities in the Cholistan Rangeland of Pakistan - Muhammad Farooq Azhar; Muhammad Junaid Faiz; Ehsan Ali; Abida Aziz; Muhammad Akbar; Ghulam Raza; Muhammad Abdullah; Muhammad Muzammil Habib; Muhammad Farooq Akram (Environmental Development, 2024)

Untapped rich microbiota of mangroves of Pakistan: diversity and community compositions - Rabia Bushra; Iftikhar Ahmed; Jia-Ling Li; Zhenghan Lian; Shuai Li; Ahmad Ali; Bushra Uzair; Arshia Amin; Muhammad Ehsan; Yong-Hong Liu; Wen‑Jun Li (Folia Microbiologica, 2024)

Novel polynomial Abet data augmentation algorithm with GRU paradigm for nuclear power prediction - Saifullah Khan; Saeed Ehsan Awan; Yasir Muhammad; Ihtesham Jadoon; Muhammad Asif Zahoor Raja (Annals of Nuclear Energy, 2024)

Assessment of water quality using entropy-weighted quality index, statistical methods and electrical resistivity tomography, Moti village, northern Pakistan - Umair Bin Nisar; Wajeeh ur Rehman; Saher Saleem; Kashif Taufail; Faizan ur Rehman; Muhammad Farooq; Siddique Akhtar Ehsan (Journal of Contaminant Hydrology, 2024)

Production of manganese telluride-based manganese oxide nano-composite works as a catalyst for effective oxygen evolution reaction - Zainab M. Almarhoon; Karam Jabbour; Sumaira Manzoor; Syed Imran Abbas Shah; Muhammad Faheem Ashiq; Muhammad Yousaf Ur Rehman; Muhammad Fahad Ehsan; Muhammad Najam-ul-Haq; Muhammad Naeem Ashiq (Fuel, 2024)

Calibrated probabilistic sub-seasonal forecasting for Pakistan’s monsoon rainfall in 2022 - Bohar Singh; Muhammad Azhar Ehsan; Andrew W. Robertson (Climate Dynamics, 2024)

Long-term evaluation of rainfall in the arid region of Pakistan using multi-source data - Ehsan Elahi; Mohammad Ilyas Abro; Murad Ali Khaskheli; Ghulam Abbas Kandhro; Tasneem Zehra; Sikandar Ali; Muhammad Najam Shaikh; Barkat Ali Laghari; Mahdi Hassan; Mushtaque Ahmed Memon (Theoretical and Applied Climatology, 2024)

Correction to: Alleviation of cadmium toxicity in pea (Pisum sativum L.) through Zn−Lys supplementation and its effects on growth and antioxidant defense - Muhammad Hamzah Saleem; Abida Parveen; Shagufta Perveen; Naheed Akhtar; Fozia Abasi; Maria Ehsan; Habib Ali; Mohammad K. Okla; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; et al. (Environmental Science and Pollution Research, 2024)

Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2024)

Alleviation of cadmium toxicity in pea (Pisum sativum L.) through Zn−Lys supplementation and its effects on growth and antioxidant defense - Muhammad Hamzah Saleem; Abida Parveen; Shagufta Perveen; Naheed Akhtar; Fozia Abasi; Maria Ehsan; Habib Ali; Mohammad K. Okla; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; et al. (Environmental Science and Pollution Research, 2024)

The application of multi-attribute decision making methods in integrated watershed management - Rana Muhammad Adnan Ikram; Sarita Gajbhiye Meshram; Mohd Abul Hasan; Xinyi Cao; Ehsan Alvandi; Chandrashekhar Meshram; Saiful Islam (Stochastic Environmental Research and Risk Assessment, 2024)

New insights on designing the next-generation materials for electrochemical synthesis of reactive oxidative species towards efficient and scalable water treatment: A review and perspectives - Amir Taqieddin; Stephanie Sarrouf; Muhammad Fahad Ehsan; Akram N. Alshawabkeh (Journal of Environmental Chemical Engineering, 2023)

Forecast skill of Bangladesh summer monsoon rainfall in C3S and NMME models after calibration - Muhammad Azhar Ehsan; Bohar Singh (Dynamics of Atmospheres and Oceans, 2023)

Geocellular Modeling of the Cambrian to Eocene Multi-Reservoirs, Upper Indus Basin, Pakistan - Muhsan Ehsan; Muhammad Ali Umair Latif; Abid Ali; Ahmed E. Radwan; Muhammad Attique Amer; Kamal Abdelrahman (Natural Resources Research, 2023)

Sembar Formation as an Unconventional Prospect: New Insights in Evaluating Shale Gas Potential Combined with Deep Learning - Muhammad Raiees Amjad; Urooj Shakir; Muyyassar Hussain; Awais Rasul; Saqib Mehmood; Muhsan Ehsan (Natural Resources Research, 2023)

Evaluation of aquifer parameters through integrated approach of geophysical investigations, pumping test analysis and Dar-Zarrouk parameters in the central part of Bari Doab, Punjab, Pakistan - Shahbaz Muhammad; Perveiz Khalid; Muhammad Irfan Ehsan; Jahanzeb Qureshi; Salman Farooq (Environmental Monitoring and Assessment, 2023)

Assessment of radiological indices and physiochemical characterization of sediments in Chashma Lake, Pakistan - Mustafa Khan; Muhammad Zaman Chaudhary; Ehsan Ullah Khan; Jawaria Abid; Tabassum Nasir; Nadeem Yaqoob (Environmental Monitoring and Assessment, 2023)

Assessment of landcover impacts on the groundwater quality using hydrogeochemical and geospatial techniques - Javed Iqbal; Gomal Amin; Chunli Su; Ehsan Haroon; Muhammad Yousuf Jat Baloch (Environmental Science and Pollution Research, 2023)

A game theory approach to land acquisition conflicts in Pakistan - Ahsan Shafi; Zhanqi Wang; Muhsan Ehsan; Faizan Ahmed Riaz; Muhammad Rashid Ali; Feng Xu (Land Use Policy, 2023)

Microplastics: unraveling the signaling pathways involved in reproductive health - Muhammad Tanveer; Nimra Mansha; Afzal Nimra; Muhammad Babar Khawar; Ali Afzal; Hanan Afzal; Muhammad Farooq; Sadia Ehsan; Rabbia Rana; Sara Shahzaman (Environmental Science and Pollution Research, 2023)

In-situ hydrogen peroxide formation and persulfate activation over banana peel-derived biochar cathode for electrochemical water treatment in a flow reactor - Jong-Gook Kim; Stephanie Sarrouf; Muhammad Fahad Ehsan; Kitae Baek; Akram N. Alshawabkeh (Chemosphere, 2023)

The relationship between carbon dioxide flux and environmental parameters at a tropical coastal sea on different timescales - Yusri Yusup; Abdulghani Essayah Swesi; Muhammad Fikri Sigid; Haitem M. Almdhun; Ehsan Jolous Jamshidi (Marine Pollution Bulletin, 2023)

Nitrogen and phosphorus change the early natural vegetation restoration in degraded Phaeozems of gullies - Ziliang Xiao; Shaoliang Zhang; Mingming Guo; Feng Zhao; Hao Wang; Weitao Xu; Muhammad Aurangzeib; Ehsan Tavakkoli (Science of The Total Environment, 2023)

Viscoacoustic One-Way Fourier Finite Difference Propagator Based on Time Fractional Viscoacoustic Wave Equation - Zhongkui Dai; Jiachun You; Muhammad Irfan Ehsan; Guangde Zhang; Huaibang Zhang; Song Tang; Zike Ma (Pure and Applied Geophysics, 2023)

Impact of green human resource management on green creativity in pharmaceutical companies: mediation role of green mindset - Muhammad Haseeb Shakil; Rana Nadir Idrees; Sadaf Ehsan; Waseem Anwar (Environmental Science and Pollution Research, 2023)

Development of Mn-MOF/CuO composites as platform for efficient electrocatalytic OER - Bushra Shabbir; Nidhal Drissi; Karam Jabbour; Abdelaziz Gassoumi; F.F. Alharbi; Sumaira Manzoor; Muhammad Faheem Ashiq; H.A. Alburaih; Muhammad Fahad Ehsan; Muhammad Naeem Ashiq (Fuel, 2023)

Hydrogeophysical modeling and physio-chemical analysis of quaternary aquifer in central part of Bari Doab, Punjab, Pakistan - Shahbaz Muhammad; Muhammad Irfan Ehsan; Perveiz Khalid; Asma Sheikh (Modeling Earth Systems and Environment, 2023)

High prevalence of extensively drug resistant and extended spectrum beta lactamases (ESBLs) producing uropathogenic Escherichia coli isolated from Faisalabad, Pakistan - Beenish Ehsan; Asma Haque; Muhammad Qasim; Aamir Ali; Yasra Sarwar (World Journal of Microbiology and Biotechnology, 2023)

Removal of Toxic Metals from Water by Nanocomposites through Advanced Remediation Processes and Photocatalytic Oxidation - Ahmad Farhan; Misbah Zulfiqar; Samiah; Ehsan Ullah Rashid; Shahid Nawaz; Hafiz M.N. Iqbal; Teofil Jesionowski; Muhammad Bilal; Jakub Zdarta (Current Pollution Reports, 2023)
Purpose of Review Heavy and toxic metals are becoming more prevalent in the water sources of the globe, which has detrimental repercussions for both human health and the health of ecosystems. The summary of recent findings on treatment possibilities of toxic metal species by nanomaterials should facilitate the development of more advanced techniques of their removal. Recent Findings The high concentrations of chromium, mercury, and arsenic identified in wastewater cause a hazard to human health. There is a wide variety of nanoadsorbents and nanophotocatalysts used for heavy/hazardous metal removal. Recent research has resulted in the production of advanced nanostructures that exhibit extraordinary heavy/hazardous metal adsorption effectiveness and photocatalytic diminution of metal ions. These nanostructures have physically and chemically tunable features. Summary In this review article, the use of carbon-based nanomaterials, polymer-based nanomaterials, and semiconductor-based nanomaterials are extensively discussed to remove mercury, chromium, and arsenic ions from wastewater by the adsorption process. Advanced nanomaterials involved in photocatalytic reduction are also comprehensively discussed.

Hydrothermal assisted synthesis of hierarchical SnO2 micro flowers with CdO nanoparticles based membrane for energy storage applications - Ehsan Ullah; Muhammad Zia Ullah Shah; Syed Awais Ahmad; Muhammad Sajjad; Shaukat Khan; Fatimah M. Alzahrani; Adel E.M. Yahya; Sayed M. Eldin; Bhargav Akkinepally; A. Shah; Shenghui Guo (Chemosphere, 2023)

Architectural complexities and morphological variations of the indus fan and its elements: Understanding of the turbidite system through seismic characterization - Ehsan ul Haq; Ji Youliang; Hadayat Ullah; Khurram Shahzad; Nisar Ahmed; Saad Ahmed Mashwani; Muhammad Zaheer (Marine and Petroleum Geology, 2023)

Algae extract delamination of molybdenum disulfide and surface modification with glycidyl methacrylate and polyaniline for the elimination of metal ions from wastewater - Saleem Raza; Muhammad Usman Hameed; Ehsan Ghasali; Asif Hayat; Yasin Orooji; Hongjun Lin; Ceren Karaman; Fatemeh Karimi; Nevin Erk (Environmental Research, 2023)

Remediation of Environmental Contaminants Through Phytotechnology - Abdul Latif; Aown Abbas; Javed Iqbal; Muhammad Azeem; Waleed Asghar; Rehmat Ullah; Muhammad Bilal; Muhammad Arsalan; Madeeha Khan; Rizwan Latif; Muhammad Ehsan; Asad Abbas; et al. (Water, Air, & Soil Pollution, 2023)

Metal ferrites-based nanocomposites and nanohybrids for photocatalytic water treatment and electrocatalytic water splitting - Ahmad Farhan; Javeria Arshad; Ehsan Ullah Rashid; Haroon Ahmad; Shahid Nawaz; Junaid Munawar; Jakub Zdarta; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2023)

Graphene-based nanoarchitectures as ideal supporting materials to develop multifunctional nanobiocatalytic systems for strengthening the biotechnology industry - Muhammad Bilal; Ehsan Ullah Rashid; Jakub Zdarta; Teofil Jesionowski (Chemical Engineering Journal, 2023)

Evaluation of Potential Predictability of Indian Summer Monsoon Rainfall in ECMWF's Fifth-Generation Seasonal Forecast System (SEAS5) - Raju Attada; Muhammad Azhar Ehsan; Prasanth A. Pillai (Pure and Applied Geophysics, 2022)

Spatial appraisal of aquifer characterization through hydrogeophysical investigations in central part of Bari Doab, Punjab, Pakistan - Shahbaz Muhammad; Perveiz Khalid; Muhammad Irfan Ehsan (Environmental Monitoring and Assessment, 2022)

Porous materials for the recovery of rare earth elements, platinum group metals, and other valuable metals: a review - Sidra Iftekhar; Golnaz Heidari; Neda Amanat; Ehsan Nazarzadeh Zare; Muhammad Bilal Asif; Mahnaz Hassanpour; Vesa Pekka Lehto; Mika Sillanpaa (Environmental Chemistry Letters, 2022)

Sedimentological and diagenetic analysis of Early Eocene Margalla Hill Limestone, Shahdara area, Islamabad, Pakistan: implications for reservoir potential - Haroon Aziz; Jabir Hussain; Muhammad Tariq; Muhsan Ehsan; Salman Khurshid; Saleem Khan; Waleed Anwar (Carbonates and Evaporites, 2022)

Comparative Transcriptomic and Metabolomic Profiling of Grapevine Leaves (cv. Kyoho) upon Infestation of Grasshopper and Botrytis cinerea - Haoran Jia; Teng Li; Muhammad Salman Haider; Ehsan Sadeghnezhad; Qianqian Pang; Jian Han; Peian Zhang; Lingyun Su; Haifeng Jia; Jinggui Fang (Plant Molecular Biology Reporter, 2022)

Application of CSM-CANEGRO Model for Climate Change Impact Assessment and Adaptation for Sugarcane in Semi-arid Environment of Southern Punjab, Pakistan - Muhammad Nadeem; Muhammad Nazer Khan; Ghulam Abbas; Zartash Fatima; Pakeeza Iqbal; Mukhtar Ahmed; Muhammad Ali Raza; Abdul Rehman; Ehsan Ul Haq; Akbar Hayat; Muhammad Ali; Shakeel Ahmad (International Journal of Plant Production, 2022)

Impact of coal rents, transportation, electricity consumption, and economic globalization on ecological footprint in the USA - Zheng Wenlong; Muhammad Atif Nawaz; Amena Sibghatullah; Syed Ehsan Ullah; Supat Chupradit; Vu Minh Hieu (Environmental Science and Pollution Research, 2022)

Environmental concerns of financial inclusion and economic policy uncertainty in the era of globalization: evidence from low & high globalized OECD economies - Sami Ullah; Kishwar Ali; Salman Ali Shah; Muhammad Ehsan (Environmental Science and Pollution Research, 2022)

Optimizing exploration of quality groundwater through geophysical investigations in district Pakpattan, Punjab, Pakistan - Shahbaz Muhammad; Muhammad Irfan Ehsan; Perveiz Khalid (Arabian Journal of Geosciences, 2022)

Radiological risk assessment in sediment of Namal Lake, Mianwali, Pakistan - Irfan Afzal; Muhammad Zaman Chaudhary; Ehsan Ullah Khan; Tabassum Nasir; Nadeem Yaqoob (Environmental Monitoring and Assessment, 2022)

Estimation of a trend of meteorological and hydrological drought over Qinhuai River Basin - Mohammad Ilyas Abro; Ehsan Elahi; Ram Chand; Dehua Zhu; Jan Muhammad; Muhammad Rafique Daudpoto; Abdul Majid Soomro; Murad Ali Khaskheli (Theoretical and Applied Climatology, 2022)

Sugarcane Breeding in Pakistan - Shahid Afghan; Waqas Raza Arshad; Muhammad Ehsan Khan; Karim Baksh Malik (Sugar Tech, 2022)

New organosulfur metallic compounds as potent drugs: synthesis, molecular modeling, spectral, antimicrobial, drug likeness and DFT analysis - Abrar Ul Hassan; Sajjad Hussain Sumrra; Muhammad Nadeem Zafar; Muhammad Faizan Nazar; Ehsan Ullah Mughal; Muhammad Naveed Zafar; Mazhar Iqbal (Molecular Diversity, 2022)

Photosynthesis research under climate change - Sajad Hussain; Zaid Ulhassan; Marian Brestic; Marek Zivcak; Weijun Zhou; Suleyman I. Allakhverdiev; Xinghong Yang; Muhammad Ehsan Safdar; Wenyu Yang; Weiguo Liu (Photosynthesis Research, 2021)

Seasonal predictability of Ethiopian Kiremt rainfall and forecast skill of ECMWF's SEAS5 model - Muhammad Azhar Ehsan; Michael K. Tippett; Andrew W. Robertson; Mansour Almazroui; Muhammad Ismail; Tufa Dinku; Nachiketa Acharya; Asher Siebert; Jemal Seid Ahmed; Asaminew Teshome (Climate Dynamics, 2021)

Convective available potential energy (CAPE) in Pakistan and its association with precipitation and temperature - Sameen Malik; Rehan Ahmed; Muhammad Latif; Muhammad Azam; Ehsan Haroon; Muhammad Bilal Iqbal (Theoretical and Applied Climatology, 2021)

Water decontamination using bio-based, chemically functionalized, doped, and ionic liquid-enhanced adsorbents: review - Ehsan Nazarzadeh Zare; Ackmez Mudhoo; Moonis Ali Khan; Marta Otero; Zumar Muhammad Ali Bundhoo; Chanaka Navarathna; Manvendra Patel; Anju Srivastava; Charles U. Pittman; Todd Mlsna; Dinesh Mohan; Pooyan Makvandi; et al. (Environmental Chemistry Letters, 2021)

An integrated approach to evaluate the unconventional hydrocarbon generation potential of the Lower Goru Formation (Cretaceous) in Southern Lower Indus basin, Pakistan - Muhsan Ehsan; Hanming Gu; Abid Ali; Malik Muhammad Akhtar; Saiq Shakeel Abbasi; Muhammad Armaghan Faisal Miraj; Munawar Shah (Journal of Earth System Science, 2021)

α-Fe2O3-based nanocomposites: synthesis, characterization, and photocatalytic response towards wastewater treatment - Rooha Khurram; Zhan Wang; Muhammad Fahad Ehsan (Environmental Science and Pollution Research, 2021)

Correction to: Water resources of Balochistan, Pakistan—a review - Malik Muhammad Akhtar; Abida Dost Mohammad; Muhsan Ehsan; Rabia Akhtar; Jalil ur Rehman; Zaira Manzoor (Arabian Journal of Geosciences, 2021)

Water resources of Balochistan, Pakistan—a review - Malik Muhammad Akhtar; Abida Dost Mohammad; Muhsan Ehsan; Rabia Akhtar; Jalil ur Rehman; Zaira Manzoor (Arabian Journal of Geosciences, 2021)

Predicting peak summer monsoon precipitation over Pakistan in ECMWF SEAS5 and North American Multimodel Ensemble - Muhammad Azhar Ehsan; Michael K. Tippett; Fred Kucharski; Mansour Almazroui; Muhammad Ismail (International Journal of Climatology, 2020)
The potential and actual forecast skill of peak summer monsoon precipitation (July–August [JA]) over the core summer monsoon region of Pakistan (CSMRP: 68°–76°E, 30°–36°N) is investigated. The predictions from the latest version of the European Centre for Medium‐Range Weather Forecast System5 (SEAS5) and the North American Multimodel Ensemble (NMME) initialized in the beginning of June, May, and April are utilized. The potential skill is estimated by signal‐to‐noise ratio and perfect model correlation. The forecast skill is evaluated using the temporal anomaly correlation as well as the ranked probability skill score for probabilistic forecasts. The SEAS5 generally captures the observed climatological mean and variability patterns of peak summer monsoon precipitation over the region, with some biases mainly located over the complex topography zones. Observed SST anomalies in the El Niño–Southern Oscillation (ENSO) region are negatively correlated with observed peak summer monsoon precipitation over the region. The ENSO–precipitation connection is weakly reproduced in SEAS5 at Lead‐1 and fades gradually with increasing lead time. The potentially predictable component (signal) is small compared to the unpredictable part (noise). Nonetheless, statistically significant potential skill is found over the CSMRP. However, the forecast skill of peak summer monsoon precipitation over the region is lower than the potential skill in SEAS5. A multimodel ensemble average of five models shows little benefit in predicting peak monsoon precipitation over Pakistan. Extended spatial averaging has some impact on the skill; however, temporal averaging has no effect on the skill of the summer monsoon precipitation in SEAS5. Together these results show limitations of the current seasonal prediction models and demonstrate their inadequate performance in predicting peak summer monsoon precipitation over Pakistan.

Potential predictability of boreal winter precipitation over central-southwest Asia in the North American multi-model ensemble - Muhammad Azhar Ehsan; Fred Kucharski; Mansour Almazroui (Climate Dynamics, 2020)

Structural styles, hydrocarbon prospects, and potential of Miano and Kadanwari fields, Central Indus Basin, Pakistan - Saif-Ur-Rehman K. Jadoon; Ding Lin; Siddique Akhtar Ehsan; Ishtiaq A. K. Jadoon; Muhammad Idrees (Arabian Journal of Geosciences, 2020)

Potential predictability of Arabian peninsula summer surface air temperature in the North American multimodel ensemble - Muhammad Azhar Ehsan; Fred Kucharski; Mansour Almazroui; Muhammad Ismail; Michael K. Tippett (Climate Dynamics, 2019)

Sub-lethal effects of lufenuron exposure on spotted bollworm Earias vittella (Fab): key biological traits and detoxification enzymes activity - Muhammad Hafeez; Saad Jan; Muhammad Nawaz; Ehsan Ali; Bahar Ali; Muhammad Qasim; G. Mandela Fernández-Grandon; Muhammad Shahid; Mo Wang (Environmental Science and Pollution Research, 2019)

Farmer Perceptions of Climate Change, Observed Trends and Adaptation of Agriculture in Pakistan - Muhammad Abid; Jürgen Scheffran; Uwe A. Schneider; Ehsan Elahi (Environmental Management, 2019)

Phytohormones enhanced drought tolerance in plants: a coping strategy - Abid Ullah; Hakim Manghwar; Muhammad Shaban; Aamir Hamid Khan; Adnan Akbar; Usman Ali; Ehsan Ali; Shah Fahad (Environmental Science and Pollution Research, 2018)

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability - Regie Lyn P. Santos-Cortez; Valeed Khan; Falak Sher Khan; Zaib-un-Nisa Mughal; Imen Chakchouk; Kwanghyuk Lee; Memoona Rasheed; Rifat Hamza; Anushree Acharya; Ehsan Ullah; Muhammad Arif Nadeem Saqib; Izoduwa Abbe; et al. (Human Genetics, 2018)

Identification of Hydrocarbon Potential of Talhar Shale: Member of Lower Goru Formation Using Well Logs Derived Parameters, Southern Lower Indus Basin, Pakistan - Muhsan Ehsan; Hanming Gu; Malik Muhammad Akhtar; Saiq Shakeel Abbasi; Zaheen Ullah (Journal of Earth Science, 2018)

Sensitivity of AGCM ‐simulated regional JJAS precipitation to different convective parameterization schemes - Muhammad Azhar Ehsan; Mansour Almazroui; Ahmed Yousef; O'Brien Enda; Michael K. Tippett; Fred Kucharski; Abdulrahman A. Alkhalaf (International Journal of Climatology, 2017)
This study examines the effects of convective parameterization schemes ( CPSs ) on the simulated June–September ( JJAS ) precipitation climatology, variability and predictability over southwestern Arabian Peninsula and northeast Africa during 1981–2014 within an atmospheric global climate model framework. The three CPSs used are: the simplified Arakawa–Schubert ( SAS ) scheme; the SAS scheme with Tokioka modification ( STOK ) and the Emanuel ( EMAN ) scheme coupled with a probability distribution function‐based cloud parameterization scheme. SAS and STOK overestimate JJAS total precipitation over the selected domain compared to observations, while EMAN underestimates. EMAN provides the most realistic distribution of precipitation and spatial distribution of convective precipitation despite the tendency for underestimating the total precipitation. The principal patterns of precipitation variability (as measured by the leading empirical orthogonal functions) in EMAN and STOK are clearly related to the observed pattern, while the maximum variability in SAS occurs in a completely different location. The El Niño Southern Oscillation‐related JJAS precipitation teleconnection simulated by the SAS scheme is very weak as compared to observations and other two CPSs . The signal‐to‐noise ratio estimated by SAS and STOK is very low as compared to EMAN . Correlation analysis shows that EMAN performs better than the other two CPSs . Low (high) outgoing longwave radiation ( OLR ) values are indicative of enhanced (suppressed) convection and hence more (less) cloud coverage. The root mean square error estimated for OLR in EMAN is lower than that of the other two CPSs . The vertical structure of specific humidity and temperature shows less error in EMAN than that of the other two CPSs , which could be a reason for better predictability over the region of interest.

Erratum to: An application of AVO derived attributes to analyze seismic anomalies of gas hydrate bearing sediments in Makran offshore, Pakistan - Muhammad Irfan Ehsan; Nisar Ahmed; Zia Ud Din; Perveiz Khalid; Liu Xue Wei (Acta Geodaetica et Geophysica, 2017)

The use of wastewater in livestock production and its socioeconomic and welfare implications - Ehsan Elahi; Muhammad Abid; Liqin Zhang; Gibson Maswayi Alugongo (Environmental Science and Pollution Research, 2017)

Skill and predictability in multimodel ensemble forecasts for Northern Hemisphere regions with dominant winter precipitation - Muhammad Azhar Ehsan; Michael K. Tippett; Mansour Almazroui; Muhammad Ismail; Ahmed Yousef; Fred Kucharski; Mohamed Omar; Mahmoud Hussein; Abdulrahman A. Alkhalaf (Climate Dynamics, 2017)

Agroforestry: a sustainable environmental practice for carbon sequestration under the climate change scenarios—a review - Farhat Abbas; Hafiz Mohkum Hammad; Shah Fahad; Artemi Cerdà; Muhammad Rizwan; Wajid Farhad; Sana Ehsan; Hafiz Faiq Bakhat (Environmental Science and Pollution Research, 2017)

Direct and indirect effects of wastewater use and herd environment on the occurrence of animal diseases and animal health in Pakistan - Ehsan Elahi; Liqin Zhang; Muhammad Abid; Muhammad Tariq Javed; Han Xinru (Environmental Science and Pollution Research, 2017)

Erratum to: An application of rock physics modeling to quantify the seismic response of gas hydrate-bearing sediments in Makran accretionary prism, offshore, Pakistan - Muhammad Irfan Ehsan; Nisar Ahmed; Perveiz Khalid; Liu Xue Wei; Mustansar Naeem (Geosciences Journal, 2016)

An application of AVO derived attributes to analyze seismic anomalies of gas hydrate bearing sediments in Makran offshore, Pakistan - Muhammad Irfan Ehsan; Nisar Ahmed; Zia Ud Din; Perveiz Khalid; Liu Xue Wei (Acta Geodaetica et Geophysica, 2016)

Analysis of geological structure and anthropological factors affecting arsenic distribution in the Lahore aquifer, Pakistan - Akhtar Malik Muhammad; Tang Zhonghua; Zakari Sissou; Bahaa Mohamadi; Muhsan Ehsan (Hydrogeology Journal, 2016)

Numerical simulation of methane plumes based on effective medium theory - Jiachun You; Canping Li; Lifang Cheng; Xuewei Liu; Muhammad irfan Ehsan (Arabian Journal of Geosciences, 2015)

Mutation of ATF6 causes autosomal recessive achromatopsia - Muhammad Ansar; Regie Lyn P. Santos-Cortez; Muhammad Arif Nadeem Saqib; Fareeha Zulfiqar; Kwanghyuk Lee; Naeem Mahmood Ashraf; Ehsan Ullah; Xin Wang; Sundus Sajid; Falak Sher Khan; Muhammad Amin-ud-Din; Joshua D. Smith; et al. (Human Genetics, 2015)

Erratum to: Sphingobacterium pakistanensis sp. nov., a novel plant growth promoting rhizobacteria isolated from rhizosphere of Vigna mungo - Iftikhar Ahmed; Muhammad Ehsan; Yeseul Sin; Jayoung Paek; Nauman Khalid; Rifat Hayat; Young H. Chang (Antonie van Leeuwenhoek, 2014)

Sphingobacterium pakistanensis sp. nov., a novel plant growth promoting rhizobacteria isolated from rhizosphere of Vigna mungo - Iftikhar Ahmed; Muhammad Ehsan; Yeseul Sin; Jayoung Paek; Nauman Khalid; Rifat Hayat; Young H. Chang (Antonie van Leeuwenhoek, 2014)

Tree species as a potential source of bio-herbicides for controlling Parthenium hysterophorus L. - Muhammad Ehsan Safdar; Asif Tanveer; Abdul Khaliq; Muhammad Shahbaz Naeem; Salman Ahmad (Natural Product Research, 2013)

Effect of diet on preweaning performance of Sahiwal calves - Shaukat Ali Bhatti; Muhammad Faisal Ahmed; Peter Charles Wynn; David McGill; Muhammad Sarwar; Muhammd Afzal; Ehsan Ullah; Musarrat Abbas Khan; Muhammad Sajjad Khan; Russell Bush; Hassan Mahmood Warriach; Ahrar Khan (Tropical Animal Health and Production, 2012)